A novel effector caspase (Caspase-3/7-1) involved in the regulation of immune homeostasis in Chinese mitten crab Eriocheir sinensis. Issue 83 (December 2018) - Qu, Chen; Yang, Wen; Xu, Qingsong; Sun, Jiejie; Lu, Mengmeng; Wang, Ying; Liu, Chao; Wang, Weilin; Wang, Lingling; Song, Linsheng
Abstract: Caspases are a conserved family of cysteine proteases characterized by specificity for aspartic acid and play an essential role in cell apoptosis. In the present study, a novel effector caspase (designated as Es Caspase-3/7-1) was identified from Chinese mitten crab Eriocheir sinensis . The open reading frame of Es Caspase-3/7-1 cDNA was of 972 bp, encoding a polypeptide of 323 amino acids. Es Caspase-3/7-1 contained an N-terminal prodomain and a conservative C-terminal CASc domain, with the conserved active site "QACRG". The mRNA transcripts of Es Caspase-3/7-1 were constitutively expressed in all the examined tissues with high expression level in hemocytes, hepatopancreas and gill. The Es Caspase-3/7-1 protein was mainly distributed in the cytoplasm of hemocytes. After Aeromonas hydrophila and lipopolysaccharide (LPS) stimulations, the mRNA expression level of Es Caspase-3/7-1 in hemocytes increased significantly. The mRNA expression level of Es Caspase-3/7-1 in hemocytes was significantly up-regulated after H2 O2 treatment in vitro . The recombinant Es Caspase-3/7-1 protein (r Es Caspase-3/7-1) was capable of hydrolyzing the substrate Ac-DEVD- p NA rather than Ac-YVAD- p NA and Ac-VEID- p NA in vitro, and exhibited binding activity to LPS. These results demonstrated that Es Caspase-3/7-1 might act as an LPS receptor, and play an important role in the regulation of immune homeostasis of E. sinensis . Highlights: Es Caspase-3/7-1 was a homolog of vertebrate effector Caspase in Eriocheir sinensis. The expression of Es Caspase-3/7-1 increased post LPS and Aeromonas hydrophila stimulations. Es Caspase-3/7-1 played vital roles during H2 O2 -induced apoptosis by cleaving PARP. r Es Caspase-3/7-1 protein exhibited Caspase-3 and LPS binding activities.